2020
DOI: 10.3390/jmmp4010017
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Heat-Treatment on the Thermal and Mechanical Stability of Ni/Al2O3 Nanocrystalline Coatings

Abstract: Heat-treatment is a frequently used technique for modifying the physical and chemical properties of materials. In this study, the effect of heat-treatment on the mechanical properties, thermal stability and surface morphology of two types of electrodeposited coatings (pure-Ni and Ni/Al2O3) were investigated. The XRD analyses showed that the crystal structure of the as-deposited coating changes from slightly amorphous to crystalline as the heat-treatment temperature increases. The heat-treatment of both the pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Modification of the surface of the titanium alloy. Each polished sample was coated with Ni coating deposited from a modified Watts Nickle bath solution 16,17 . The electrodeposition process was carried out in a 250 ml glass beaker.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Modification of the surface of the titanium alloy. Each polished sample was coated with Ni coating deposited from a modified Watts Nickle bath solution 16,17 . The electrodeposition process was carried out in a 250 ml glass beaker.…”
Section: Methodsmentioning
confidence: 99%
“…Various particle sizes are visible in the SEM micrograph within the particle clusters. Previous studies on these materials suggested particle agglomeration occurred in the as-received powders 17,20 .…”
Section: Shielding Gasmentioning
confidence: 97%